Pembelajaran Teknik Tonguing pada Instrumen Flute dalam Mata Kuliah Praktik Instrumen Mayor Tiup - Viandika Rizki Septiadi; Esy Maestro (SENDRATASIK UNP, 2022)
The purpose of this study is to find out how the process of Learning Tonguing Techniques on flute Instruments in the Wind Major Instrument Practice Course in the UNP Music Education Study Program. In this study, an analytical descriptive method was used by utilizing qualitative data. The research instrument in this thesis is the researcher himself. In the implementation of Tonguing Technique Learning on flute Instruments in the Wind Major Instrument Practice Course in the Music Education Study Program UNP involves students of the class of 2021 who have just taken the wind instrument major 1 practice course. Learning outcomes are that students are able to understand some of the basic things of learning wind instruments properly and correctly. The tonguing technique is one of the basic techniques in the game of flute instruments and is one of the things that must be considered in flute instrument games. The tonguing technique had a great influence in the game of flute instruments. So in this case the researcher examines the learning process of the tonguing technique on the flute instrument by looking for the process, learning experience and learning evaluation.